Analisis Kesalahan Siswa dalam Menyelesaikan Soal Sistem Persamaan Linier Dua Variabel di Kelas IX SMP Negeri 1 Lembah Seulawah - Rifa Nabillah; M Ikhsan; M Hasbi (Jurnal Peluang, 2020)
Mathematics is a branch of science that has a vital role in the development of science and technology. Mathematical literacy is a non-negotiable ability needed today. However, mathematics remains complicated for students to understand; many students make mistakes in solving math problems, including the SLETV material. A student should follow Polya's steps (understanding the problem, planning a solution, implementing a predetermined plan, and reviewing the results that have been obtained). This study aimed to determine the mistakes made by students and the factors causing Grade IX students of SMP Negeri 1 Lembah Seulawah to make mistakes in solving SLETV problems. This research is descriptive qualitative research. The subjects in this study were 6 Grade IX students of SMP Negeri 1 Lembah Seulawah, Aceh Indonesia. Data collection was conducted in paper-based tests and interviews. The instruments were paper-based tests and interviews. The data were analyzed using the procedures proposed by Miles and Huberman: data reduction, data presentation, and drawing conclusions. This study indicates that Grade IX students of SMP Negeri 1 Lembah Seulawah generally have not been able to understand and plan the solution of the problems given correctly in solving SLETV problems. The cause of errors is that students are not used to systematically working on mathematical problems, and some students misunderstand the concepts of elimination and substitution.